PERSEPSI KARYAWAN TENTANG KOMUNIKASI DAN PRODUKTIVITAS PADA PERUSAHAAN MANUFAKTUR DAN JASA DI JAKARTA - Yolanda Masnita Siagian (Universitas Trisakti, 2002)
Most of the manager's time confiscated for communication activity, but there are several barriers to reach it. An effective communication very determine to the success of the company, which show by increased productivity. There are several factors to get satisfied communication, i.e: Communication Climate, Media Quality, Supervisory Communication, Organizational Information, Personal Feed back, Subcoordinate Communication. In manufacture and service company, the considered factors will be different